2018
DOI: 10.1001/jamaophthalmol.2018.2373
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Morphologic Characteristics in Patients With Down Syndrome

Abstract: IMPORTANCE Literature suggests corneal morphologic characteristics compatible with keratoconus are present in a high percentage of patients with Down syndrome (DS), suggesting the need to perform a detailed examination of the anterior segment to try to avoid serious visual impairment in this group of patients. OBJECTIVE To characterize the abnormal features of the cornea in patients with DS and compare these with a control group. DESIGN, SETTING, AND PARTICIPANTSMulticenter case-control study at Vissum Alicant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 30 publications
7
69
1
Order By: Relevance
“…Several studies have reported variable rates for the prevalence and incidence of KC in DS patients, which may be due to the lack of standard criteria for KC diagnosis in DS [ 11 ]. As demonstrated in this study (Tables 1 and 4 ), the DS-C group differed from the age- and gender-matched non-DS NC group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported variable rates for the prevalence and incidence of KC in DS patients, which may be due to the lack of standard criteria for KC diagnosis in DS [ 11 ]. As demonstrated in this study (Tables 1 and 4 ), the DS-C group differed from the age- and gender-matched non-DS NC group.…”
Section: Discussionmentioning
confidence: 99%
“…This difference, in addition to age and genetic predisposition, can be due to diagnostic criteria. Given these uncertainties in the diagnosis, the term KC-compatible has been used to describe findings, and it has been shown that 71.3% of DS patients may have findings suggestive of KC [ 11 ]. Given the lack of literature on this topic, this study was designed in an attempt to define diagnostic criteria for differentiating KC and KCS from non-ectatic corneas in DS patients.…”
Section: Introductionmentioning
confidence: 99%
“…6 ORASIS Eye Clinic, Swiss Eye Research Foundation, Reinach, Switzerland. 7 Department of Physics, Faculty of Sciences, University of Novi Sad, Novi Sad, Serbia. 8 Faculty of Medicine of the Military Medical academy, University of Defense, Belgrade, Serbia.…”
Section: Fundingmentioning
confidence: 99%
“…Patients who intensely rub their eyes (e.g. those with Down Syndrome and atopic patients are at higher risk of developing keratoconus [ 4 , 7 9 ]. The reasons to rub their eyes are manifold: itchiness in atopic conjunctivitis represents one of the most common causes of eye rubbing [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 The widely used standard Dresden solution requires a 30-min infiltration of riboflavin solutions followed by 30 min of UV irradiation (3 mW∕cm 2 , 5.4 J∕cm 2 ). 3 However, it is difficult for some patients, for example, children and patients with Down syndrome (a disease highly associated with keratoconus), 4 to keep themselves focused on the target over a 30-min treatment. According to the Bunsen-Roscoe law, the same effect can be achieved theoretically with an equal radiant energy provided by less intense UV radiation over a longer period of time or a more intense UV radiation over a shorter period of time.…”
Section: In Vivo Evaluation Of Corneal Biomechanical Properties By Opmentioning
confidence: 99%